2017
DOI: 10.1063/1.4999906
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation dynamics of the ortho- and para-xylyl radicals

Abstract: The photodissociation dynamics of the CH isomers ortho- and para-xylyl are investigated in a free jet. The xylyl radicals are generated by flash pyrolysis from 2-(2-methylphenyl)- and 2-(4-methylphenyl) ethyl nitrite and are excited into the D state. REMPI- spectra show vibronic structure and the origin of the transition is identified at 32 291 cm for the para- and at 32 132 cm for the ortho-isomer. Photofragment H-atom action spectra show bands at the same energy and thus confirm H-atom loss from xylyl radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 58 publications
1
31
1
Order By: Relevance
“…271,272 Ion imaging studies of the H atoms formed by photolysis of o-and p-xylyl radicals at wavelengths  ~310 nm and ~250 nm are similarly consistent with C-H bond fission after IC to the ground state PES. 273 These data all serve to illustrate the extent of isomerisation (ring opening and H atom transfer) that is required after accessing the ground state PES in order to sample the lowest energy fragmentation pathways. But these studies also return H atom formation rates that, whilst still slow, are considerably (one or more orders of magnitude) faster than predicted by RRKM calculations for the fully thermalized ground state radical at the relevant excitation energy.…”
Section: Phenyl Benzyl and Larger Aromatic Radicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…271,272 Ion imaging studies of the H atoms formed by photolysis of o-and p-xylyl radicals at wavelengths  ~310 nm and ~250 nm are similarly consistent with C-H bond fission after IC to the ground state PES. 273 These data all serve to illustrate the extent of isomerisation (ring opening and H atom transfer) that is required after accessing the ground state PES in order to sample the lowest energy fragmentation pathways. But these studies also return H atom formation rates that, whilst still slow, are considerably (one or more orders of magnitude) faster than predicted by RRKM calculations for the fully thermalized ground state radical at the relevant excitation energy.…”
Section: Phenyl Benzyl and Larger Aromatic Radicalsmentioning
confidence: 99%
“…But these studies also return H atom formation rates that, whilst still slow, are considerably (one or more orders of magnitude) faster than predicted by RRKM calculations for the fully thermalized ground state radical at the relevant excitation energy. 271,273 Might this be a hint that, even in these larger radicals and over these longer timescales, the decay of the 'hot' ground state species is influenced by the dynamical process(es) by which they are formed? In terms of energy disposal at least, this photophysical behaviour appears to extend to heteroaryl radicals also.…”
Section: Phenyl Benzyl and Larger Aromatic Radicalsmentioning
confidence: 99%
“…Recently, the hydrogen loss dynamics of o-and p-xylyl were investigated, albeit details on the electronic structure remained unexplored. 16 In addition, the ground states of the xylyl cations have been probed by PE spectroscopy 48 and, more accurately, by threshold photoelectron (TPE) spectroscopy, 15 yielding ionization energies and vibrational frequencies. In order to understand the fast deactivation mechanisms in flames and reactors, a more profound picture of the electronic structure, including high lying excited states, has to be established if laser excitation is used to trigger chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Special attentions were paid on the decomposition reactions of o-xylyl radical. Based on available theoretical [3,[33][34][35] and experimental [36][37][38][39] progresses and analogy to benzyl reactions, detailed o-xylyl decomposition pathways were incorporated in the present model. The pathways include its decomposition to oxylylene and H, decomposition to fulvenallene and methyl, 2-methylfulvenallene and H, 1,3cyclopentadiene and methylcyclopentadienyl via ring-rearrangement reactions, decomposition to benzocyclobutene via ring-closure reaction, decomposition to benzyl via H-attack reaction and isomerization to m-xylyl or dimethylphenyl.…”
Section: Kinetic Model Developmentmentioning
confidence: 99%
“…Rate constants of these reactions were referred to similar reactions of benzyl. Pachner et al [33] suggested that o-xylylene can isomerize to styrene or benzocyclobutene and the latter is more energetically favoured. Benzocyclobutene can also isomerize to styrene.…”
Section: Kinetic Model Developmentmentioning
confidence: 99%